Curbing Child Marriage amongst Muslims in Malaysia: Towards Legal Reform - Samuri, Mohd Al Adib; Mohd Awal, Noor Aziah; Abu Bakar, Muhamad Abral (UUM Press, 2022)
Child marriage is considered by the international community to be a violation of human rights, particularly the right to education and sexual and reproductive healthcare. Unfortunately, there are some Muslim countries in the world, including Malaysia, that has legalized this practice. Laws such as the Islamic family laws in all Malaysian states stipulate legal avenues for underage children to get married, provided they obtain permission from the Sharia court. Therefore, in order to end this harmful practice in Malaysian Muslim society, this article will discuss child marriage under Malaysian Islamic family law and propose a legal reform for Islamic family law regarding marriageable age and court procedure. This article examined international law instruments related to child marriage, Malaysian civil and Islamic laws, and reported cases to understand the legal complexities of child marriage in Malaysia. This article found that there is an urgent need for international agencies, Malaysian federal and state governments, religious authorities, and civil society movements to commence initiatives that address this issue to curb child marriage amongst Muslims in Malaysia, particularly through reforming Islamic family law in all states.